Picture Book Legenda Ki Rangga Gading Sebagai Media Pembelajaran Anak (Program Studi Pendidikan Seni Rupa FBS UNJ, 2021)
Along with the development of the era of oral folklore fading, causing many children who do not recognize it. Therefore, the artist takes a Thesis on the Creation of Fine Art Works with the title